Governance And Its Impact On Textile Companies - Garcia Vargas, Ma. de Lourdes Elena; Sanchez Trujillo, Magda Gabriela (European Scientific Journal, ESJ, 2016)
From an economic perspective, the flaws and weaknesses of the government seem to be more evident because of situations such as vagueness of the boundaries between governments and public policies that make it harder work in an attempt to regulate activities of companies to generate small effective numbers and productive trade relations. To know the situation in the textile sector a diagnostic was carried out in 17 companies in production, technological development areas and university services, with an exploratory and quantitative study, and transeccional design. Afterwards were given a qualitative perspective with action research design when applying interviews with government representatives, and advisory councils, chambers of commerce to establish their participation in finding solutions in relations to the problems observed: distrust of the business sector programs offered by the government, minimal participation in training and innovation forums in Consultation Councils and in the decision-making process which prevent the sector increase its development.